2017
DOI: 10.1111/jocn.13799
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of a delirium prevention and management programme

Abstract: Registered nurses in South Korea should need not only appropriate education, but also adequate resources, policies and guidelines as well as support from managers and from all other healthcare professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Four studies reported that CPD on the topic resulted in healthcare professionals feeling more confident and competent in identifying and managing delirium in the older person (Akinjogbin et al., 2020; Fick et al., 2018; Kang et al., 2017; Rosen et al., 2013). Healthcare professionals in fifteen studies requested more delirium training to include consequences of undiagnosed delirium, assessment tools, hypoactive delirium, delirium superimposed on dementia and other underlying cognitive impairments and care management (Akintade et al., 2011; Alhaidari & Allen‐Narker, 2017; Campioni‐Norman & Vizcaychipi, 2017; Emme, 2020; Hosie et al., 2015; Kai‐Chung Wong et al., 2018; Kang et al., 2017; LaMantia et al., 2017; Merkin et al., 2014; Randles et al., 2018; Rosen et al., 2013; Ryan & Milligan, 2017; Schonnop et al., 2022; Van de Steeg et al., 2014; Wang & Mentes, 2009). A lack of CPD on the topic meant that healthcare professionals found it difficult to administer and interpret delirium assessment tools (Alhaidari & Allen‐Narker, 2017; Hosie et al., 2015; Kai‐Chung Wong et al., 2018; Kang et al., 2017; Rice et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies reported that CPD on the topic resulted in healthcare professionals feeling more confident and competent in identifying and managing delirium in the older person (Akinjogbin et al., 2020; Fick et al., 2018; Kang et al., 2017; Rosen et al., 2013). Healthcare professionals in fifteen studies requested more delirium training to include consequences of undiagnosed delirium, assessment tools, hypoactive delirium, delirium superimposed on dementia and other underlying cognitive impairments and care management (Akintade et al., 2011; Alhaidari & Allen‐Narker, 2017; Campioni‐Norman & Vizcaychipi, 2017; Emme, 2020; Hosie et al., 2015; Kai‐Chung Wong et al., 2018; Kang et al., 2017; LaMantia et al., 2017; Merkin et al., 2014; Randles et al., 2018; Rosen et al., 2013; Ryan & Milligan, 2017; Schonnop et al., 2022; Van de Steeg et al., 2014; Wang & Mentes, 2009). A lack of CPD on the topic meant that healthcare professionals found it difficult to administer and interpret delirium assessment tools (Alhaidari & Allen‐Narker, 2017; Hosie et al., 2015; Kai‐Chung Wong et al., 2018; Kang et al., 2017; Rice et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare professionals in fifteen studies requested more delirium training to include consequences of undiagnosed delirium, assessment tools, hypoactive delirium, delirium superimposed on dementia and other underlying cognitive impairments and care management (Akintade et al., 2011; Alhaidari & Allen‐Narker, 2017; Campioni‐Norman & Vizcaychipi, 2017; Emme, 2020; Hosie et al., 2015; Kai‐Chung Wong et al., 2018; Kang et al., 2017; LaMantia et al., 2017; Merkin et al., 2014; Randles et al., 2018; Rosen et al., 2013; Ryan & Milligan, 2017; Schonnop et al., 2022; Van de Steeg et al., 2014; Wang & Mentes, 2009). A lack of CPD on the topic meant that healthcare professionals found it difficult to administer and interpret delirium assessment tools (Alhaidari & Allen‐Narker, 2017; Hosie et al., 2015; Kai‐Chung Wong et al., 2018; Kang et al., 2017; Rice et al., 2011). For example, it was difficult to evaluate the CAM items ‘acute onset’, ‘inattention’, ‘disorientation’ and ‘altered consciousness’ (Kai‐Chung Wong et al., 2018; Rice et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The healthcare team, including nurses should be cognisant of the general and population specific risk factors for delirium, the variations in presentation identified as delirium and the documentation and communication of the symptoms within the team, so that the appropriate treatment strategies and evidence‐based delirium prevention interventions could be implemented (see, e.g., McDonnell & Timmins, ). The current literature is, however, not just addressing limited awareness on delirium, its risk factors and symptoms, but also attributed lack of relevant formal and ongoing education among nurses and physicians (Kang, Moyle, Cooke, & O'Dwyer, ; McDonnell & Timmins, )…”
Section: Introductionmentioning
confidence: 99%